Association between Prepregnancy Body Mass Index and Gestational Weight Gain with Size, Tempo, and Velocity of Infant Growth: Analysis of the Newborn Epigenetic Study Cohort - Fuemmeler, Bernard F. (Child Obes, 2016)
Background: The first 1000 days of life is a critical period of infant growth that has been linked to future adult health. Understanding prenatal factors that contribute to variation in growth during this period could inform successful prevention strategies. Methods: Prenatal and maternal characteristics, including prepregnancy obesity and gestational weight gain were evaluated in relation to weight growth trajectories during the first 24 months of life using the SuperImposition by Translation and Rotation (SITAR) method, which provides estimates of infant size, timing to peak velocity, and growth velocity. The study sample included 704 mother-infant dyads from a multiethnic prebirth cohort from the Southeastern United States. The total number of weight measures was 8670 (median number per child = 14). Results: Several prenatal and maternal characteristics were linked with infant growth parameters. The primary findings show that compared to women with a prepregnancy BMI between 18 and 24.9, women with a prepregnancy BMI ≥40 had infants that were 8% larger during the first 24 months, a delayed tempo of around 9 days, and a slower velocity. Mothers who had greater than adequate gestational weight gain had infants that were 5% larger even after controlling for prepregnancy BMI and several other covariates. Conclusions: The findings contribute new data on the associations between gestational weight gain and aspects of early growth using the SITAR method, and support a growing consensus in the literature that both prepregnancy BMI and gestational weight gain relate independently to risk for greater postnatal weight growth.